Management consulting : a guide to the profession - Kubr, Milan (ed.) (Geneva : International Labour Office, 1977)
In this book, consulting is viewed primarily as a method for improving management practice
"Training films": p. 367-369.
Includes bibliographies.
ijb, 18/01/2019
Loans
Keywords: Business consultants